Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Ulang Produk Customcase Handphone dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Tntshop3 Semarang) - Saputri, Dian Mutiara; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2016)
This study aim to analyze the effect of variants product, perceptions of price and service quality to repurchase intention in Tntshop3 products through customer satisfactions as intervening variable on product users Tntshop3. Variants products, perceptions of price and service quality are the reasons of consumer when selecting and alsho repurchasing customcase mobile phone products which is one of important consumer needs.In this case use three independent variables with one intervening variables and the dependent variable. The population are customers Tntshop3. This research uase as a sample of 100 respondents by the criteria have been using the services of Hest'in Modiste more than twice. Then the data were analyzed using multiple regression analysis channeled through the SPSS program. Based on the research results, the result that variants product, perceptions of price and service quality positive effect on customer satisfaction with the regression coefficient is Y1 = 0,212X1+0,218X2+0,498X3 and customer satisfaction has positive effect on the repurchase intention with the regression coefficient is Y2 = 0,693Y1+e.